MANAJEMEN LABA DAN KAS DI TANGAN: EFEK MODERASI DARI KENDALA KEUANGAN - Vina Elfreda; Ari Budi Kristanto (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2020)
Global economic’s uncertainty that occurs cause a predictions of an economic crisis that may happen anytime. This prediction becomes the basis for corporates to anticipate, which one of them by increasing corporate cash holding. The amount of cash holding can be determined with earnings management, especially in this global economic uncertainty. The purpose of this study is to investigate the effect of earnings management on cash holding with financial constraint as moderating variables. The samples of this study are collected by purposive sampling and resulted 363 companies as the final sample from manufaturing companies listed in the Indonesia Stock Exchange in 2016-2018. Data were analyzed by using panel data regression. The result shows that earning management has positive and significant effect on cash holding. In addition, financial constraint is also proven to moderate by strengthening the effect of earning management towards cash holding